HUMAN LANGUAGE VS ANIMAL COMMUNICATION : CONSTRUCTION, INTEGRATION THEORY DESIGN FEATURE OF LANGUAGE - Samosir, Deswita Fitriani; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2024)
This study aims to compare and contrast human language with animal communication, focusing on their construction, integration, and design features based on language theories. While human language is complex, flexible, and capable of abstract thought, animal communication systems are often considered more limited, relying on instinctual signals. By examining key theoretical frameworks, including Charles Hockett's